How European identity could frame intercultural dialogue in the EU - García-Faroldi, Livia (My University, 2013)
Many factors influence attitudes towards Europeans from other state members or towards the EU integration process. Two of them are national contexts and the interaction between National and European identity. On the one hand, National frames could be more or less inclusive and help or make more difficult to establish an intercultural dialogue with other National cultures. On the other hand, people who feel European as an important part of their identity tend to establish more easily dialogue with other European or non-European cultures, and could be concerned in a greater extent for the future of the countries more affected by the crisis and for the EU as a whole. The economic crisis we are experiencing since 2008 is testing the extent of trust and solidarity among Europeans. Governments and citizens from richer countries, less affected by the crisis, have helped poorer states with many conditions. Both solidarity and trust are crucial to define a “sense of community”, this sense requires mutual trust, a “we-feeling” and a partial identification in terms of self-images and interests (Deutch, 1957). Economic crisis has remarked that the European Union is far away from being a political community, where citizens feel that they are Europeans and take care of each other. European identity, then, has been threaten by the economic crisis and this makes intercultural dialogue in Europe more difficult.
Keywords: Identidad colectiva; EU; Intercultural dialogue; European Identity